Hunter syndrome: case report and review of literature (2006)
Hunter syndrome is one of the mucopolysaccharidosis, which are a rare group of genetic diseases, It is due to a deficiency in the enzyme Iduronate 2-sulphatase. This in turn leads to the accumulation of glycosaminoglycans, dermatan and heparan sulphate. The intra and extracellular accumulation of this substances lead to multisystemic organ abnormality. We present a patient with Hunter syndrome who presented with involvement of the skin, cardiovascular system, the eyes and musculoskeletal system. We have also included a literature review. As far as we know, it is the first case reported in a Nigerian.